Gender Engagement Differences with Remote Learning: A Middle Level Teacher's Perspective - Matt Chandler (Middle Grades Review, 2020)
This essay shares the perspective of a sixth grade teacher working with students during a period of remote learning. Gender engagement data from multiple classrooms is presented. In addition, other research is cited to raise questions and concerns about student engagement equity during a period of remote learning.
Keywords: remote learning; gender; equity